PARENTERAL TREATMENTS INVOLVING AMINOADAMANTANE DERIVATIVES - Patel, Kalpana; Singh Sachdeva, Gurpartap; Borsadia, Suresh; Raval, Krunal (2023)
A method and composition is described for treating impaired neurological function, CNS disease or condition, including altered state of consciousness disorders in a human subject, comprising parenterally administering a composition comprising aminoadamantane derivatives or salts thereof, alone or in combination with other neuroprotective and/or anti-inflammatory compounds, in a pharmacologically effective amount. In some embodiments, a method for treating traumatic brain injury caused by a stroke or an accident in a human subject is provided comprising intravenously administering a composition comprising amantadine hydrochloride in a pharmacologically effective amount to the subject in need thereof.